Searching for authenticity - Baugh, S. Gayle; Sullivan, Sherry E., 1961- (Research in careers, 2015)
Volume 2 of the Research in Careers series focuses on the search for authenticity in one's career. Although there has been growing interest in the topic within the popular press, relatively little academic research has been completed on authenticity and careers. Researchers are still refining the concept of authenticity and are just beginning to investigate how it influences the enactment of careers in today's turbulent career landscape. This volume offers the first organized effort on the topic.